THE ROUTE DETERMINATION OF FILING A TAXI TO THE CUSTOMER IN TERMS OF FUNCTIONING OF THE AUTOMATED CONTROL SYSTEM - Davidich, Yu. O.; Ponkratov, D. P. (Science and Transport Progress, 2008)
The issues of overall performance increase of taxi transport due to improvement of automated system of dispatching management by its technological processes are considered. The route of taxi submission to a customer is offered to be determined by a criterion of minimum time. To solve the given task the taxi submission route determination technique is developed. It will promote the reduction of passengers’ waiting time and the decrease in operational expenses of a carrier.